2004
DOI: 10.1677/joe.0.1820353
|View full text |Cite
|
Sign up to set email alerts
|

Prohormone convertase 1 (PC1) processing and sorting: effect of PC1 propeptide and proSAAS

Abstract: Prohormone convertase 1 (PC1) is a serine proteinase responsible for the proteolytic processing of many precursor proteins within the regulated secretory pathway. The activity of PC1 is potentially regulated by two endogenous inhibitors, the PC1 propeptide and proSAAS. Here we have investigated the effect of proSAAS and propeptidecontaining constructs on PC1 carboxy-terminal processing and activity. In AtT-20 cells, proSAAS expression inhibited both C-terminal PC1 processing and proopiomelanocortin (POMC) proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…9). PC1/3, the cleavage enzyme that produces ACTH and α-MSH from POMC, is activated by proteolytic cleavage of its C-terminal tail (Lee, et al 2004). We were able to detect the expression of the partially active 84 kD and the inactive 97 kD form in aortic mesenchymal progenitors and the highly active 66 kD form of PC1/3 in the murine macrophage (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…9). PC1/3, the cleavage enzyme that produces ACTH and α-MSH from POMC, is activated by proteolytic cleavage of its C-terminal tail (Lee, et al 2004). We were able to detect the expression of the partially active 84 kD and the inactive 97 kD form in aortic mesenchymal progenitors and the highly active 66 kD form of PC1/3 in the murine macrophage (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the dominant inheritance did not result in the full scope of endocrinopathies associated with PC1/3 null patients, confirming residual PC1/3 activity. As described above, the inhibitory function of PC1/3 prodomain was already established in vitro (54,56,57). The earlier described PCSK1-p.G209R mutant which was shown to retain the PCSK1-p.P258T hypomorph in the ER, could have a similar limited dominant negative effect (89).…”
Section: B Heterozygous Mutations Contribute To Obesitymentioning
confidence: 99%
“…Evaluation of treatments over the long term will determine whether the beneficial effects of PCSK9 inhibition on LDL-C levels will directly translate into coronary artery disease risk reduction [70][71][72] . Chen et al [72] identified PCSK9 as a specific SEC24A-dependent COPII cargo: indeed as trans-membrane and soluble proteins co-translationally inserted into the endoplasmic reticulum (ER), it is packaged into transport vesicles coated with coat protein complex Ⅱ (COPⅡ) for the export from the ER and the delivery to the Golgi for further processing [73] . Chen et al [72] reported that complete deficiency of SEC24A is compatible with normal development and survival in mice.…”
Section: Inhibition Of Pcsk9mentioning
confidence: 99%